Secretion from acinar cells of the exocrine pancreas: role of enteropancreatic reflexes and holecystokinin - Singer, Manfred V.; Niebergall-Roth, Elke (Cell biology international, 2009)
Although the molecular machinery and mechanism of cell secretion in acinar cells of the exocrine pancreas is well documented and clear, only recently has the pharmacophysiology of pancreatic exocrine secretion come to light. Therefore, we focus in this article on the current understanding of the pharmacophysiology of pancreatic exocrine secretion. The pancreatic secretory response to ingestion of a meal is mediated via a complex interplay of neural, humoral and paracrine mediators. A major role in the control of the intestinal phase of pancreatic secretion is attributed to vago-vagal enteropancreatic reflexes. In the scheme of this control mechanism, afferents originating in the duodenal mucosa, and efferents mediating central input on the pancreatic ganglia, activate intrapancreatic postganglionic neurons. Experiments utilizing specific receptor antagonists demonstrate the involvement of both muscarinic M1 and M3 receptors expressed in pancreatic acinar cells. Cholecystokinin (CCK), originally implicated in the humoral secretion of pancreatic enzymes, through a direct action on acinar CCK receptors, is also essential to the enteropancreatic reflex mechanism. CCK stimulation of the exocrine pancreatic secretion through excitation of sensory afferents of the enteropancreatic reflexes, is a paracrine mode of CCK action, and is probably the only one in humans and the predominant one in rats. In dogs, however, CCK acts on the pancreas via both the humoral and a paracrine route. More recent experiments suggest further possible sites of CCK action. Additionally, at the brain stem, vago-vagal enteropancreatic reflexes may be modulated by input from higher brain centres, particularly the hypothalamic-cholinergic system in the tonic stimulation of preganglionic neurons of the dorsal motor nucleus of the vagus projecting into the pancreas.